Block Chain Technology in Supply Chain Management: A Review (International Journal of Innovative Research in Engineering & Management, 2021)
Blockchain technology has a wide range of applications,  including supply chain management (SCM), where it may  replace mid-size activities in many transaction-based processes  throughout the supply chain. Blockchain technology has a  disruptive effect on the growth and operation of the supply  chain, making it extremely essential to investigate future  possibilities for usage. Supervision and monitoring are  becoming very complex as proper utilization become  increasingly globalized. Blockchain platform, as a decentralized  digitized advanced technologies that assures accountability,  authenticity, and privacy, has the capacity to solve various  global supply chain administration concerns. Distributed supply  chain coordination, material and data flow coordination, virtual  companies, agile supply chain management, supply chain  management flexibility, supply chain measurement, supply  chain resilience, risk and reel effect, real-time controls, and  supply chain-based service are all technical potential problems  associated with blockchain advancement discussed in this study.  This research looks at a variety of sectors, including shipping,  manufacturing, and automotive, aviation, finance, technology,  energy, health, food and farming, e-commerce, and education, to  see how blockchain technology may help with visibility and  business process management. In addition to future theoretical  studies, technical and engineering research is critical for a  variety of supply chain issues.
Keywords: Application; Blockchain; Management; Supply Chain; Transactions